The Embodiment of Mahakrya Lango Film - I Nyoman Payuyasa; Nyoman Lia Susanthi; I B. Hari Kayana Putra (Institut Seni Indonesia Denpasar, 2022)
The Indonesian Institute of the Arts Denpasar (ISI Denpasar) is an arts college in Bali that is established based on the values of local wisdom and national insight in order to enrich human values. ISI Denpasar seeks to strengthen media literacy to campaign for the heritage of cultural arts values through audio-visual media to the public. In order to support the presence of this audio-visual media, the author conducted research and created a short film with the title Mahakrya Lango. Mahakrya Lango is a short film that is strengthened by a poetic narrative. In short, this film covers the journey of Balinese art and culture, the hustle and bustle of Bali, the oblivion of heritage, to the presence of ISI Denpasar as an art and cultural advisory institution. In its embodiment, this film takes several main visuals with a water background set as a symbol of the source of life, flexibility, dynamism, firmness, to fragility. The film creation method uses three stages, namely pre-production, production, and post-production. In the embodiment of the Mahakrya Lango film, the location set is Tamblingan Lake to visualize water as a source of life, waterfalls to symbolize flexibility and dynamism, and beach locations to depict celebrations.